Synthesis of Novel (Polymer Blend-Titanium Carbide) Nanocomposites and Studying their Characterizations for Piezoelectric Applications (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Piezoelectric nanocomposites are very important for many applications as a pressure sensors. Fabrication of (polyvinyl alcohol - polyvinyl pyrrolidinone -titanium carbide) nanocompos- ites and study their structural, electrical, dielectric and optical properties have been in- vestigated. The effect of adding the TiC nanoparticles on structural, electrical, dielectric and optical properties of polymeric blend has been studied. The results showed that the electrical conductivity of (PVA-PVP-TiC) nanocomposites is increasing with the increase of TiC nanoparticles concentrations at room temperature. The FTIR analysis showed there is no interactions between (PVA- PVP) polymer blend and TiC nanoparticles. The dielectric studies showed the dielectric constant and dielectric loss of nanocomposites increase with the increase of TiC nanoparticles concentrations and they decrease as frequency increased. The A.C electrical conductivity increases with the increase of TiC nanoparticles concentra- tions and frequency. The results of optical properties showed that the optical absorbance of (PVA- PVP) polymer blend increases with the increase of TiC nanoparticles concentrations. The optical constants change with increase in TiC nanoparticles concentrations. The piezo- electric application results of (PVA-PVP-TiC) nanocomposites showed that the electrical resistance of (PVA-PVP-TiC) nanocomposites decreases with an increase of the pressure which make it is suitable for piezoelectric applications or pressure sensors.